High D-dimer levels predict cardiovascular events in patients with chronic atrial fibrillation during oral anticoagulant therapy - Vene, Nina; Mavri, Alenka; Košmelj, Katarina; Stegnar, Mojca (Thrombosis and Haemostasis, 2003)
Atrial fibrillation (AF) is associated with hemostatic abnormalities and increased risk of thrombotic cardiovascular events even during oral anticoagulant therapy (OAT). The aim of our study was to evaluate the predictive value of hemostatic markers for the risk of major cardiovascular events during OAT. The study group comprised 113 patients with chronic AF (70.2 ± 5.4 years old, 60% men), referred for OAT. Established clinical risk factors and levels of prothrombin fragment 1+2 (F1+2), thrombin-antithrombin complexes (TAT), D-dimer, tissue plasminogen activator (t-PA) and plasminogen activator inhibitor 1 (PAI-1) antigen and activity, before and during OAT (after 3.9 ± 0.7 months; INR 2.57 ± 0.57) were determined. In all patients OAT significantly suppressed levels of F1+2 by 67%, TAT by 30% and D-dimer by 48% (all p <0.001). During an average follow-up of 44 months 22/111 (20%) patients suffered a combined cardiovascular event (stroke, myocardial infarction, peripheral vascular occlusion or vascular death). Patients with cardiovascular events were significantly older, had more frequent heart failure/systolic dysfunction and had significantly increased levels of D-dimer at entry (63 vs 39 ng/mL, p = 0.005) and during OAT (33 vs 18 ng/mL, p = 0.002), and of t-PA antigen at entry (14.3 vs 10.9 ng/mL, p = 0.02) and during OAT (15.0 vs 11.2 ng/mL, p = 0.05) (all values are medians). In multivariate Cox proportional hazard models, heart failure/systolic dysfunction (hazard ratio 2.91; 95% CI 1.17-7.26; p = 0.02), high levels of D-dimer on OAT (top vs. lower two quartiles) (hazard ratio 4.78, 95% CI 1.39-16.41; p = 0.01) and t-PA antigen levels (continuous variable) (hazard ratio 1.09; 95% CI 1.01-1.17; p = 0.02) were significantly associated with combined cardiovascular events.In conclusion, high levels of D-dimer and t-PA antigen during OAT are significant predictors of combined cardiovascular events in AF patients and, on this basis, could be useful additional markers of cardiovascular risk in such patients.
Keywords: Atrial fibrillation; oral anticoagulant therapy; coagulation; fibrinolysis